Genetic background affects pathogenicity island function and pathogen emergence in Streptomyces. (9th February 2018) - Zhang, Yucheng; Jiang, Guangde; Ding, Yousong; Loria, Rosemary
Summary: With few exceptions, thaxtomin A (ThxA), a nitrated diketopiperazine, is the pathogenicity determinant for plant‐pathogenic Streptomyces species. In Streptomyces scabiei (syn . S. scabies ), the ThxA biosynthetic cluster is located within a 177‐kb mobile pathogenicity island (PAI), called the toxicogenic region (TR). In S. turgidiscabies, the ThxA biosynthetic cluster is located within a 674‐kb pathogenicity island (PAIst). The emergence of new plant pathogens occurs in this genus, but not frequently. This raises the question of whether the mobilization of these pathogenicity regions, through mating, is widespread and whether TR and PAIst can confer plant pathogenicity. We showed that ThxA biosynthetic clusters on TR and PAIst were transferred into strains from five non‐pathogenic Streptomyces species through mating with S. scabiei and S. turgidiscabies . However, not all of the transconjugants produced ThxA and exhibited the virulence phenotype, indicating that the genetic background of the recipient strains affects the functionality of the ThxA biosynthetic cluster and therefore would be expected to affect the emergence of novel pathogenic Streptomyces species. Thxs have been patented as natural herbicides, but have yet to be commercialized. Our results also demonstrated the potential of the heterologous production of ThxA as a natural and biodegradable herbicide in non‐pathogenic Streptomyces species.